Extracorporeal Shock Wave Lithotripsy and Combined Therapy in Children: Efficacy and Long-Term Results - Burgos Lucena, Laura; Fernández Bautista, Beatriz; Parente Hernández, Alberto; Ortiz Rodríguez, Ruben; Angulo Madero, Jose María (Frontiers in Pediatrics, 2021)
Background: Extracorporeal shock wave lithotripsy (ESWL) is nowadays the first choice for the treatment of upper urinary tract stones smaller than 2 cm, considering its low complications and high success rate. Aim: To present an update of the current situation of ESWL treatment and to analyse our series of patients and the efficacy of combined lithiasis treatment in different locations and sizes. Patients and method: Retrospective study including patients with urolithiasis treated with ESWL between 2007-2019. Collected data included: gender and age at treatment, presentation symptoms, imaging studies, stone location and size, complications and stone clearance. Success was defined as stone-free status or the presence of clinically insignificant residual fragments (<4 mm after 3 months follow-up). Patients with residual stones larger than 4 mm after 3 months were programmed for another ESWL session or received a combined sandwich therapy, followed by URS or percutaneous approach. Results: Between 2007 and 2019, 37 patients presented a total of 41 lithiasis episodes that were treated with ESWL sessions. Median age at first procedure was 9 years old (1-17) and median follow-up time was 6 years (3-12). Stones were located in the renal pelvis, followed by the lower, middle and upper calyx, proximal ureter, and 51% of our patients had multiple lithiasis. Median stone size was 12 mm (5-45), the main component being calcium oxalate (34%). During immediate postoperative period, 8 patients (19%) presented complications: renal colic, hematuria and urinary tract infection. After the first ESWL, 41% of the patients (n=17) were stone-free. Out of the 24 residual lithiasis episodes (58%), 3 patients (7%) underwent a second ESWL session. In the remaining 19 patients, ESWL was combined with URS or percutaneous approach to achieve complete stone clearance. Overall stone free status after combined therapy was 95% (n=39). Conclusion: These data support that ESWL is an effective minimally invasive technique, with low cost and morbidity, reproducible and safe for the treatment of stone disease in children. Even though lithiasis size seems to be a significant factor in ESWL success, in combination with other lithotripsy procedures it can reach very high rates of stone clearance.